Eco-friendly Zeolite Synthesis for Phenol Adsorption: Kinetic and Isotherm Studies - Yahya, Kawthar; Moussa, Jihed; Boussai, Khawla; Lissir, Boulanoir; Hamdi, Noureddine (Global Journal of Earth Science and Engineering, 2025)
The presence of phenolic compounds in aquatic systems has become a significant environmental concern due to their toxicity and persistence. This study evaluates the effectiveness of synthetic zeolites as adsorbents for removing phenol from contaminated aqueous solutions. The adsorbent was synthesized from natural clay using ZnCl₂ as an activating agent through a straightforward three-step process: (i) calcination at 90°C, (ii) aging for 24 hours, and (iii) crystallization for 8 hours. The synthesized material was then characterized by X-ray diffraction (XRD) to determine its mineralogical composition and the crystalline structure of the zeolite. The efficiency of phenol removal was assessed as a function of adsorbent dosage (0.1 g.L⁻¹ to 0.3 g.L⁻¹), contact time (20 to 60 minutes), and initial phenol concentration (500 mg.L⁻¹ to 5000 mg.L⁻¹). The adsorption kinetics were analyzed using pseudo-first-order and pseudo-second-order models, while equilibrium data were fitted to the Freundlich and Langmuir isotherm models. The results confirmed the successful synthesis of FAU-X zeolite from smectitic-kaolinitic clay. The zeolite-based adsorbent demonstrated high efficiency in phenol removal, exhibiting a sorption capacity of 125 mg.g⁻¹ after 60 minutes. The adsorption process followed pseudo-second-order kinetics, while equilibrium data were best described by the Langmuir isotherm model, indicating a monolayer adsorption pattern. The retention of pollutants was primarily governed by chemical interactions, including hydrogen bonding and electrostatic attraction between phenol molecules and the adsorbent surface. This study highlights the potential of synthesizing cost-effective zeolite-based adsorbents for wastewater treatment, contributing to the development of sustainable and environmentally friendly remediation technologies.
Keywords: Clay; Phenol; Zeolite; Adsorption; Alkaline fusion